Measuring Higgs CP and couplings with hadronic event shapes - Englert, Christoph; Spannowsky, Michael; Takeuchi, Michihisa (Journal of high energy physics, 2012)
Experimental falsification or validation of the Standard Model of Particle Physics involves the measurement of the CPCP \mathcal{C}\mathcal{P} quantum number and couplings of the Higgs boson. Both Atlas and Cms have reported an SM Higgs-like excess around m H = 125 GeV. In this mass range the CPCP \mathcal{C}\mathcal{P} properties of the Higgs boson can be extracted from an analysis of the azimuthal angle distribution of the two jets in pp → H jj events. This channel is also important to measure the couplings of the Higgs boson to electroweak gauge bosons and fermions, hereby establishing the exceptional role of the Higgs boson in the Standard Model. Instead of exploiting the jet angular correlation, we show that hadronic event shapes exhibit substantial discriminative power to separate a CPCP \mathcal{C}\mathcal{P} even from a CPCP \mathcal{C}\mathcal{P} odd Higgs. Some event shapes even show an increased sensitivity to the Higgs CPCP \mathcal{C}\mathcal{P} compared to the azimuthal angle correlation. Constraining the Higgs couplings via a separation of the weak boson fusion and the gluon fusion Higgs production modes can be achieved applying similar strategies.